2006
DOI: 10.1111/j.1365-2966.2005.09803.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen formation on porous dust grains

Abstract: Recent laboratory experiments on interstellar dust analogues have shown that H 2 formation on dust-grain surfaces is efficient in a range of grain temperatures below 20 K. These results indicate that surface processes may account for the observed H 2 abundance in cold diffuse and dense clouds. However, high abundances of H 2 have also been observed in warmer clouds, including photon-dominated regions (PDRs), where grain temperatures may reach 50 K, making the surface processes extremely inefficient. It was sug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 64 publications
(90 reference statements)
0
21
0
Order By: Relevance
“…However, with careful experimental design and the use of simulations to reproduce the conditions in the ISM, as performed by Katz et al (1999) and Biham and Lipshtat (2002), the efficiency of H 2 formation in the ISM can be obtained from experimental kinetic data. Further work by the Biham's group studied the effect of particle size (Lipshtat and Biham, 2005) and porosity (Perets and Biham, 2006) on H 2 formation in interstellar environments. Diffusion of H atoms was included in the simulations of the formation kinetics (Katz et al, 1999), revealing that the ratio of the energy barrier for H atom diffusion to the binding energy is considerably higher than the typically assumed value (∼ 0.3 ) for physisorbed atoms on single crystal surfaces (Bruch et al, 2007b).…”
Section: Silicate Surfacesmentioning
confidence: 99%
“…However, with careful experimental design and the use of simulations to reproduce the conditions in the ISM, as performed by Katz et al (1999) and Biham and Lipshtat (2002), the efficiency of H 2 formation in the ISM can be obtained from experimental kinetic data. Further work by the Biham's group studied the effect of particle size (Lipshtat and Biham, 2005) and porosity (Perets and Biham, 2006) on H 2 formation in interstellar environments. Diffusion of H atoms was included in the simulations of the formation kinetics (Katz et al, 1999), revealing that the ratio of the energy barrier for H atom diffusion to the binding energy is considerably higher than the typically assumed value (∼ 0.3 ) for physisorbed atoms on single crystal surfaces (Bruch et al, 2007b).…”
Section: Silicate Surfacesmentioning
confidence: 99%
“…It would indeed appear that a more complex surface model is required to explain the efficient formation of molecular hydrogen in diffuse clouds. The effect of porosity has been considered by Perets & Biham (2006) and found to be small. Recently, we showed that on a "rough" surface, with sites on which adsorbates can have different binding energies, molecular hydrogen can be formed efficiently over a wider range of temperature (Chang et al 2005;Cuppen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To model the impact of the porous structures of interstellar grains, we introduce two types of sites: the non-porous, and the porous sites, following Perets & Biham (2006). The non-porous sites form a smooth surface that is perfectly regular, where particles interact directly with the gas phase.…”
Section: Porositymentioning
confidence: 99%
“…As previously discussed, the presence of pores creates traps for the molecules and atoms on the grain surfaces, leading to an enhancement of reactivity on the grains. GRAINOBLE includes pores, following the treatment of Perets & Biham (2006). The number and area of the pores are treated as parameters (Sect.…”
Section: B) Porosity Of the Grainsmentioning
confidence: 99%